A history of a kidnapping: From Church to Brand. Historical development of universities in Spain - Simancas González, Esther (2016)
In this brief summary of the evolution of the universities in Spain, we aim to prove that they have been saphed by the influenced of the Church, State and Capitalism. Capitalism has tried, through different educational reforms, to take ownership of the question that universities should be asking, by adding in their management new models of communiaction and marketing. This process is an attempt to legitimize the commodification of the Higher Education, leaving universities at the mercy of the market place. In this context, we can create and articulate a counter hegemonic narrative lead by the logic of participation and democracy.